The National Idea Of Modern Russia In The Official And Party Discourse - Vladimirovna Bakhlova, Olga; Vladimirovich Bakhlov, Igor; Ivanovna Izergina, Nina; Gennadyevna Napalkova, Irina; Grigor’evna Uliashkina, Ekaterina (Opción, 2019)
The objective of this research lies in the evaluation of the possible options for the conceptualization of the Russian national idea at the current stage of development. Methods. Traditional and formalized document analysis, systemic and comparative analysis, political diagnostics, expert surveys and focus groups have been used as basic research methods. Main results. The results of this research show the remaining multi-layered and controversial character of the existing versions and interpretations of the Russian national idea. A few key plots and paradigms have been established in this area. They focus on the idea of patriotism (the official discourse), the topics of “restoration” of the “great power status” (the party discourse), the ideas of “justice”, “the state of the whole people”, “the Eurasian mission” (experts) and the symbiosis of national patriotic and patriarchal paternalistic keynotes (the population). However, these ideas are shared by most Russian people to a varying degree and represent the basis of social discourse. Conclusions. Systematization of discourse practices, research data, assessments and expert recommendations draws attention to the correlation between the concepts “national idea” and “state idea” and the necessity to rethink the postmodernist interpretations of utilitarian and technocratic approaches. Taking into account the local experience and modern challenges, the essence of the Russian national idea can be expressed by the triad “Justice. Patriotism. Faith.” In the course of its implementation, it is extremely important not to underestimate the complexity of the population composition and the form of government. The novelty of this research consists in consideration of the interrelation between the internal and external dimensions of the national idea and its semantic field in the context of overlapping multicomponent factors.